The Role of Psychological Empowerment in Mediating the Effect of Transformational Leadership on Innovative Work Behavior - Darman; Putrianti, Flora Grace; Yahya, Siskawaty; Djou, Sitti Husna Noviana; Musa, Maman (West Science Business and Management, 2025)
This study explores the mediating role of psychological empowerment in the relationship between transformational leadership and innovative work behavior (IWB) in Indonesia. Using a quantitative approach, data were collected from 165 employees across various sectors. Constructs were measured using a Likert scale (1–5) and analyzed through Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results reveal that transformational leadership significantly influences both psychological empowerment and IWB. Furthermore, psychological empowerment mediates the relationship between transformational leadership and IWB, highlighting its critical role in fostering innovation. These findings emphasize the importance of leadership strategies that enhance psychological empowerment to drive innovation in the workplace. The study provides theoretical insights and practical recommendations for managers and policymakers aiming to cultivate innovative cultures within organizations.